Hepatotoxicity Comparison of Crude and Licorice-Processed Euodiae Fructus in Rats With Stomach Excess-Cold Syndrome - Zhang, Min; Gao, Meng; Wu, Shanshan; Zhou, Lifen; Cao, Lan; Qiao, Rifa; Zhong, Minyong; Yang, Lin; Yuan, Jinbin (Frontiers in Pharmacology, 2021)
In recent years, drug-induced Liver injury (DILI) has become an important issue of public health. Euodiae Fructus (EF) is a clinical commonly used herb with slightly toxicity, and large dose of EF can cause significant liver damage. Licorice-processing might reduce the hepatotoxicity of CEF (crude EF). But up to now, the studies on the hepatotoxicity of EF are very restricted, let alone its material basis and mechanism of detoxification by licorice-processing. This work firstly established a stomach excess-cold syndrome animal model by intragastric administration of cold Zhimu (Anemarrhena asphodeloides Bge). Secondly, multiple approaches and indexes were used to evaluate the hepatotoxicity of the drugs on the rats including the general behaviors, biochemical analysis, protein expressions and histopathological examination. Thirdly, the hepatotoxicity of 3 doses of three extracts of CEF and LPEF (licorice-processed EF) were systematically investigated, and the differences in hepatotoxicity were analyzed and compared comprehensively between the different extracts, three doses, CEF and LPEF. Finally, the connotation of detoxification of EF by licorice-processing was preliminarily discussed according to the toxic components and their changes after processed, toxicological characteristics and TCM (Traditional Chinese Medicine) theory. All extracts of EF were found to have dose-dependent hepatotoxicity, and the toxicity was in the order of water extract, ethanol extract and volatile oil. The hepatotoxic mechanism of EF may be related with peroxidation damage, inflammatory reaction factor and mitochondrial injury. The hepatotoxicity of CEF can be significantly reduced by licorice-processing. EF should be safe for short-term use at pharmacopoeia dose under the guidance of TCM theory. The detoxification mechanism may be related to the reduction of toxic components and antagonistic action of licorice.